About the Image of the Shaman which Studied on the Mountain Morguzar - Furkat Eshboevich , Toshboev; Farrukh Shavkatovich, Akchayev (International Journal of Psychosocial Rehabilitation, 2020)
In this article the author provides information on the meaning of the image of the Morguzar ridge of the Turkestan Mountains, the image of the rock "God Sang" in the Uriklisoy Gorge, and the images of the man and the wolf beside it. The image of the Turkic people in this image, the hair of the back, the wolf and the man, the place of the wolf totem, the people of this monument, the cultural processes that took place during the Turkic Kaganate, and the Shamanic belief among the people of Ustrushana are still preserved today. After analyzing the appearance, he came to the conclusion that the image looks like a shaman.